REDD+ Implementation in Asia and the concerns of indigenous peoples. - Thailand. Asia Indigenous Peoples Pact ([Chiang Mai, Thailand] Asia Indigenous Peoples Pact, 2011)
28-page publication on Indigenous Peoples and REDD in Asia's country participants. Provides a good overview of the status of REDD in each country and on Indigenous Peoples legal recognition within those countries. Published by Asia Indigenous Peoples Pact (AIPP).
The Situation of Forest Dependent Ethnic minorities in Vietnam and their concerns on REDD+ -- Indigenous Peoples and REDD+ in Lao PDR -- The status of REDD+ Readiness Phase implementation and the concerns of indigenous peoples in Thailand -- Situation of Indigenous Peoples in the REDD+ process in Nepal -- Status of REDD+ Implementation and the Concerns of Indigenous Peoples in Indonesia.
Cover title.
Includes bibliographic references (p. [26])
Keywords: Reducing Emissions from Deforestation and Forest Degradation; Climate change mitigation -- Developing countries -- Asia; Deforestation -- Asia; Forest policy -- Asia; Indigenous people -- Asia